The other marriage: de facto union, homosexual marriages, marriages of convenience - Santos Díez, José Luis (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2018)
The sociological increase of the diverse ways of establishing the family in Spain apart from the canonical marriage (de facto unions, homosexual marriage) offers the occasion to specify their precise legal situation and the consideration they deserve from the point of view of the canonical norms.
Keywords: marriage; de facto union; homosexual union; gipsy marriage; marriage of convenience